Construction of interval polynomial ensure the specified degree of robust stability; International Automatic Control Conference - CACS 2014, Kaohsiung, Taiwan, 26-28 Nov., 2014 - Ezangina T. A. Tatiana Aleksandrovna (2014, 2014)
Title screen